Bedrock Erosion Surfaces Record Former East Antarctic Ice Sheet Extent. Issue 9 (9th May 2018) - Paxman, Guy J. G.; Jamieson, Stewart S. R.; Ferraccioli, Fausto; Bentley, Michael J.; Ross, Neil; Armadillo, Egidio; Gasson, Edward G. W.; Leitchenkov, German; DeConto, Robert M.
Abstract: East Antarctica hosts large subglacial basins into which the East Antarctic Ice Sheet (EAIS) likely retreated during past warmer climates. However, the extent of retreat remains poorly constrained, making quantifying past and predicted future contributions to global sea level rise from these marine basins challenging. Geomorphological analysis and flexural modeling within the Wilkes Subglacial Basin are used to reconstruct the ice margin during warm intervals of the Oligocene‐Miocene. Flat‐lying bedrock plateaus are indicative of an ice sheet margin positioned >400–500 km inland of the modern grounding zone for extended periods of the Oligocene‐Miocene, equivalent to a 2‐m rise in global sea level. Our findings imply that if major EAIS retreat occurs in the future, isostatic rebound will enable the plateau surfaces to act as seeding points for extensive ice rises, thus limiting extensive ice margin retreat of the scale seen during the early EAIS. Plain Language Summary: The Wilkes Subglacial Basin is a large, low‐lying topographic depression situated beneath the Antarctic Ice Sheet. Because the land surface of the basin is currently situated below sea level, it is a potential site of ice sheet collapse and rapid retreat in a warming world. Understanding this landscape and how it has evolved through time in relation to past climate and sea level is therefore key to understanding the future dynamics of this part of the ice sheet. Here we report the discovery, using ice‐penetrating radar data sets, of extensive subglacial bedrock plateaus within the Wilkes Subglacial Basin. We analyze the geomorphology of these plateau surfaces and reconstruct the evolution of the subglacial landscape through time. Our results indicate that this part of the Wilkes Subglacial Basin was free of ice for extensive and prolonged periods of time during the early stages of ice sheet development. These constraints on past ice sheet extent, together with our landscape reconstruction, can be used by the ice sheet modeling community to better understand the likely future dynamics of this part of the Antarctic Ice Sheet. Key Points: We report the discovery of plateau‐like erosion surfaces within the Wilkes Subglacial Basin in East Antarctica Geomorphology and elevation of the plateaus are consistent with an early ice margin situated >400–500 km inland for extended periods If future major ice sheet retreat into the basin occurs, isostatic rebound will enable the plateaus to act as seeding points for ice rises